Comparison of the Physical and Technical Demands of Cricket Players During Training and Match-Play. Issue 3 (March 2018) - Vickery, Will; Duffield, Rob; Crowther, Rian; Beakley, David; Blanch, Peter; Dascombe, Ben J.
Abstract : Abstract: Vickery, W, Duffield, R, Crowther, R, Beakley, D, Blanch, P, and Dascombe, BJ. Comparison of the physical and technical demands of cricket players during training and match-play. J Strength Cond Res 32(3): 821–829, 2018—This study aimed to determine which training method (net-based sessions or center-wicket simulations) currently used in national level and U19 male players cricket provided a more physical and technical match-specific training response. The heart rate, rating of perceived exertion, and movement patterns of 42 male cricket players were measured across the various training and match formats. Video analysis was coded retrospectively to quantify technical loads based on the cricket skills performed. Magnitude-based inferences were based on the standardization of effect and presented with ±90% confidence intervals. Regardless of playing position, differences in physiological demands between training modes and match-play were unclear, with the exception of higher heart rates in fielders during traditional net sessions (mean heart rate: d = −2.7 [−4.7 to −0.7]; 75% of maximum heart rate: d = −1.7 [−3.2 to −0.2]). Typically, the movement demands of center-wicket simulations were similar or greater than match-play, which was most evident in the distance traveled at a high intensity within each playing position (batsmen: d = 6.4 [3.7–9.2]; medium-fast bowlers: d = 1.71 [0.1–3.3]; spin bowlers: d = 6.5 [0.01–13.0]; fielders: d = 0.8 [−0.2 to 1.7]). The technical demands of traditional net cricket training exceeded that of a typical match for each playing position. Specifically, fast bowlers delivered a greater number of balls during net-bowling compared with a match ( d = −2.2 [−3.6 to 0.9]). In conclusion, center-wicket simulations more closely matched the physical demands of a One-Day match within batsmen and spin bowlers, whereas traditional cricket training often exceeded match-specific demands.